Incorporation of an intact dimeric Zr12 oxo cluster from a molecular precursor in a new zirconium metal–organic framework. Issue 22 (26th February 2018) - Bezrukov, Andrey A.; Törnroos, Karl W.; Le Roux, Erwan; Dietzel, Pascal D. C.
Abstract : A dimeric Zr12 oxo cluster was used as new molecular building block in construction of metal–organic frameworks utilizing the precursor approach. Abstract : Two zirconium–organic frameworks were synthesized by exchanging the acetate ligands in [Zr12 O8 (OH)8 (CH3 COO)24 ] with polydentate linkers. Partial substitution of acetate groups by a phosphine based linker yielded a new porous framework with this unique dimeric Zr12 cluster unit as molecular building block. More exhaustive substitution of acetate resulted in cleavage of the Zr12 unit and formation of UiO-67.